Nitric oxide and thyroid carcinoma: A review - Huang, Yu; Suguro, Rinkiko; Hu, Wei; Zheng, Jiayu; Liu, Yawen; Guan, Mingxin; Zhou, Na; Zhang, Xin (Frontiers in Endocrinology, 2023)
Thyroid carcinoma is the most common endocrine cancer in the world, and its incidence has been steadily increasing in recent years. Despite its relatively good prognosis, therapies have not improved greatly in recent years, so exploring new therapies is a necessary task. Nitric oxide (NO) is a short-term endogenous signaling molecule that plays a vital role in various physiological and pathological processes and is synthesized by nitric oxide synthase (NOS). Many studies have been conducted over the past decades to explain its correlation to cancer. NO exerts a wide range of effects on cancer, involving angiogenesis, apoptosis, cell cycle, invasion, and metastasis. It also serves a dual function by promoting and halting tumor development simultaneously. The relationship between NO and thyroid carcinoma has been intensively studied and discussed. This paper reviews the role and molecular mechanism of NO in thyroid carcinoma and discusses potentials of prevention and treatment of thyroid carcinoma.